The Environmental Literacy of Lower Secondary School Pupils, High School and College Students - Kubiatko, Milan (Journal of Environmental Science and Engineering Technology, 2014)
It is general known fact, the environment problems are still more and more serious. So the environmental education is the important way, how to learn pupils and students about environment and its protection. The main aim of the study was to find out the environmental literacy level of lower secondary school pupils, high school students and college students. Next the influence of age, gender, residence and other variables was determined. The samples size was created by 245 respondents. As the research tool was used Children’s Responsible Environmental Behavior Scale (CREBS). The methods of descriptive (mean score, standard error) and inferential statistics (ANOVA) for the data analysis were used. The Cronbach’s alpha was used for the determination of the reliability. The results showed relatively low level of environmental literacy. Higher level of environmental literacy had boys in comparison with girls, next respondents from village in comparison with respondents from town and also the oldest respondents.